Industrial Training Report: Melaka Public Library / Siti Hasanah Mohamed Yusoff - Mohamed Yusoff, Siti Hasanah (Faculty of Information Management, 2018)
Industrial training is one of the requirements that needed to be fulfilled in order to obtain the Bachelor of Information Science (Hons.) Library Management (IMC690). Each students need to do the industrial training for five months in respective library and this is compulsory which is intended for the student exposure to real working environment. A good plan, proper implementation and evaluation can helps in in develop the student professional attitude. It also develop a deep understanding of problem solving skills in real situations for the students. On top of that, the industrial training also can helps in developing positive self-esteem among students and exposed the students with work ethic and professionalism as well. During the industrial training in Melaka Public Library, most of the theoretical knowledge gained in the class are being applied during carried out the tasks given. Various work process in the library especially in book processing was studied and understood during the industrial training. The industrial training gave me a good experience from the view of implementing my theoretical knowledge into the practical aspects. It gave me the experience of working in the library environment. The industrial training program is very helpful in developing my interpersonal, communication and working skills.